2021
DOI: 10.1038/s41398-021-01641-y
|View full text |Cite
|
Sign up to set email alerts
|

ECT-induced cognitive side effects are associated with hippocampal enlargement

Abstract: Electroconvulsive therapy (ECT) is of the most effective treatments available for treatment-resistant depression, yet it is underutilized in part due to its reputation of causing cognitive side effects in a significant number of patients. Despite intensive neuroimaging research on ECT in the past two decades, the underlying neurobiological correlates of cognitive side effects remain elusive. Because the primary ECT-related cognitive deficit is memory impairment, it has been suggested that the hippocampus may p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 67 publications
1
13
0
1
Order By: Relevance
“…Our data showed that ECT, not HF-rTMS, impairs cognitive function with the decline of MoCA scores ( Figures 4A,B ). The results are consistent with previous studies, which have found that ECT potentially has detrimental cognitive side effects, including amnesia and slowing of reaction times ( 48 , 49 ). Furthermore, HF-rTMS could reverse the cognitive impairment induced by ECT ( Figures 4A,B ).…”
Section: Discussionsupporting
confidence: 93%
“…Our data showed that ECT, not HF-rTMS, impairs cognitive function with the decline of MoCA scores ( Figures 4A,B ). The results are consistent with previous studies, which have found that ECT potentially has detrimental cognitive side effects, including amnesia and slowing of reaction times ( 48 , 49 ). Furthermore, HF-rTMS could reverse the cognitive impairment induced by ECT ( Figures 4A,B ).…”
Section: Discussionsupporting
confidence: 93%
“…ECT, however, is frequently associated with cognitive adverse effects, including transient cognitive impairment and memory deficits [149,150]. TMS is based on the electromagnetic induction principle:…”
Section: Non-invasive Brain Stimulation Techniquesmentioning
confidence: 99%
“…ECT entails the induction of generalized cerebral seizures under general anesthesia, producing brain chemistry changes by influencing neurogenesis, neurotrophic signaling, and neuroplasticity [ 148 ]. ECT, however, is frequently associated with cognitive adverse effects, including transient cognitive impairment and memory deficits [ 149 , 150 ]. TMS is based on the electromagnetic induction principle: focal electromagnetic pulses penetrate the skull through a wire coil to focally stimulate target areas by inducing secondary electric current flows modulating neuronal firing rates [ 151 ].…”
Section: Somatic Interventionsmentioning
confidence: 99%
“…Recent studies have found potential roles of oxidative stress, inflammation, neurotrophic factors, immunological factors, hormones, alterations in electrical brain activity, permeability of the blood brain barrier, brain perfusion, changes in functional networks with a lag of integration of new neurons and volume changes of the hippocampus. 9 , 84 , 85 Further study of the worthwhile pharmacological interventions in this review may help elucidate the mechanisms of cognitive side effects in ECT. In addition, the study of novel candidates may contribute to further understanding of these mechanisms.…”
Section: Discussionmentioning
confidence: 99%